PERCEPTION OF USEFULNESS AND EASE OF INTEREST IN USING SHARIA FINTECH - Salim, Amir; Eva Susanti; Doly Nofiansyah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
The aim of the research is to analyze perceptions of usefulness and ease of use fintech sharia among S2 STEBIS IGM Palembang students. The population in this study were STEBIS IGM students with a total research population of 314 students and female students. According to Arikunto, the sample taken for research was 314 x 25% = 78.5 rounded up to 79 students. The analysis technique uses multiple linear regression with hypothesis testing, namely the T test and F test. The findings from the results show that the perceived usefulness variable (X1) has a positive and significant effect on interest in using fintech sharia. Perceived convenience variable (X2) has a positive and significant effect on interest in using fintech sharia (Y). Simultaneously variable perceived usefulness (X1) and the perception of convenience (X2) has a positive and significant effect on interest in using fintech sharia (Y). The conclusion of this research is that both partial and simultaneous variables of perceived usefulness (X1) and the perception of convenience (X2) has a positive and significant effect on interest in using fintech sharia (Y)